Pharmacokinetics of oral versus intravenous ibuprofen for closure of patent ductus arteriosus: A pilot randomised controlled study. (3rd September 2021) - Edison, Priyantha Ebenezer; Chen, Sylvia; Yeo, Cheo Lian; Allen, John C; Poon, Woei Bing; Baral, Vijayendra R; Chowbay, Balram
Abstract : Aim: This pilot study aimed to compare the pharmacokinetic profiles of oral (PO) and intravenous (IV) ibuprofen for treatment of patent ductus arteriosus (PDA) in preterm neonates. Methods: In a single‐centre, parallel, randomised open‐label trial, neonates ≤35 weeks, weight <1800 g with haemodynamically significant PDA during the first week of life were recruited between June 2017 and February 2019 and randomised to receive either PO or IV ibuprofen at standard dosage of 10, 5 and 5 mg/kg every 24 h for three consecutive days. Plasma concentrations of ibuprofen were quantified using a validated high‐performance liquid chromatography method and pharmacokinetic parameters were calculated. Treatment outcomes were recorded. Results: Eleven neonates participated in the trial, six and five patients receiving PO and IV ibuprofen, respectively. Pharmacokinetic analysis reveals similar ibuprofen exposure levels in treatment groups. Median dose‐ and weight‐normalised C max values of PO and IV groups were 2.12 and 2.53 g/mL respectively ( P =  0.082) and median AUC0‐24 levels were comparable (PO: 34.6 g*h/mL vs. IV: 50.7.6 g*h/mL, P  = 0.25). Conclusion: This exploratory study demonstrates comparable pharmacokinetics of PO and IV formulations of ibuprofen in preterm neonates. Larger prospective studies are required to validate these findings.